(untitled) (KYAMC Journal, 2020)
Background: Preterm labour is a major cause of maternal mortality in our country. Hypomagnesaemia during pregnancy could be an indirect cause of preterm labour. Magnesium has a role on uterine smooth muscle relaxation, which is the basis for the use of magnesium sulphate as a tocolytic agent. Objective: This study was done to see the effect of magnesium sulfate to prevent preterm labour and perinatal outcome. Materials and Methods: This study was carried out in Comilla Medical College & Hospital, from December 2011 to May 2012. Fifty pregnant women, both primi and multi with preterm labour were selected for the study. Results: Study showed labour delayed >24 hours in 86% cases. And the majority of newborn (96%) had Apgar score in 5 minute was 8-10, 4% had Apgar score 7-8. The mode of delivery was vaginal in 70% cases and by c/s in 16% cases; among subject whose labour delayed more than 24 hours. Conclusion: Intravenously administration of magnesium sulfate is safe, well tolerated and effective tocolytic agent for prolongation of pregnancy in preterm labour. It produces minimal harmful effects on mother and fetus. KYAMC Journal Vol. 11, No.-3, October 2020, Page 145-149